Modélisation numérique du Friction Stir Welding - Bastier, Arnaud; Maitournam, M. Habibou; Van, Ky Dang; Roger, Frédéric (European Journal of Computational Mechanics, 2006)
This paper presents a computationnal method of a simulation of the Friction Stir Welding process. The first step of the simulation uses an eulerian approach of the thermomechanical problem. A finite element model is used to establish the temperature field based on a viscoplastic behaviour and experimental data. The second step of the simulation is more original. The calculation is based on a steady state algorithm. It takes into account the whole mechanical history of the material since the algorithm is based on an integration along the trajectories of the particles. Residual state is evaluated for a Friction Stir Welded assembling. Only the stationnary phase of the process is simulated during these two steps which confers a substantial gain of the computation time.